Studi Literatur : Konsep Pendidikan Humanisme menurut Gus Dur Relevansinya dengan Pendidikan Dasar - Herlina, Tika; Kamidjan, Kamidjan; Fitra Raharja, Hawwin (IJPSE : Indonesian Journal of Primary Science Education, 2021)
Education is used as a medium to improve skills, create character and build a dignified nation. In addition, the aim of education is to develop devotion to God Almighty and students so that they are able to become believers, healthy, noble, creative, responsive, knowledgeable, and make a society responsible and democratic so that they can humanize their fellow human beings. The flow of globalization has an impact on the existence of a human crisis of trust, characters, harmony, and morals. Humanism as proposed by KH. Abdurrahman Wahid, aimed to struggle the human values which are the benchmarks in humanism education. The aim of this research is to know the concept of humansim education according to KH. Abdurrahman Wahid who is associated in basic education. This type of research used was a library research. It is a research with data collection techniques conducted in the field (library). The data collection technique used was documentation, while the data analysis used was descriptive and hermeneutic methods. From the results, it can be concluded that humanism education based on KH Abdurrahman Wahid is the education of religious humanism, upholding human values on the basis of religion. There is an element to "humanize humans", developing all the skills that exist in humans intellectually and religiously without leaving the existing religious values. If it is related to basic education, it is very relevant because early planting of moral values, social ethics, tolerance, mutual respect, educating character to be humanist, fair in order to make a better life. So as to create students who have intellectual knowledge, humanism and religion and are useful for their nation and religion.